Sekwencyjność rozwoju stosunków GATT/ WTO z krajami rozwijającymi się - Zajaczkowski, Małgorzata (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2014)
The aim of the paper is to present the sequences of development of relations between developing countries and the institutions like GATT and WTO. First, I attempted to answer the question on what are the causes lying behind the weak activities of developing countries within the GATT and their rising participation in the final stage of the GATT’s operation. Second, I focused on the role and signifi‑ cance of developing countries within the WTO multilateral talks called the Doha Development Round. Undoubtedly the guarantee of their growing significance in the ongoing WTO multilateral negotiations is a condition for reaching the final agreement. Nevertheless it is more difficult to get approval to new stage of trade liberalisation from developing countries due to creation of numerous coalitions and groups of interests consisting of developing countries that allow them to bet‑ ter and more efficiently defend their interests. Their impact on is much stronger comparing to the GATT period and their active participation in international trading system enable them to meet their objectives and fulfil their interests.